1991
DOI: 10.1136/jnnp.54.8.731
|View full text |Cite
|
Sign up to set email alerts
|

Monosporium apiospermum meningoencephalitis: a clinico-pathological case.

Abstract: Twenty nine cases of central nervous system infection due to Monosporium apiospermum have been reported. Six of them occurred after an aspiration pneumonia following a near drowning. The case of a 53 year old man is reported: M apiospermum was isolated from cerebrospinal fluid, sputum, urine and from the mud of the ditch where the patient had fallen. Though the treatment used recommended doses of intravenous, intrathecal and intraventricular amphotericin B, it was ineffective and the patient died 97 days after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 8 publications
0
20
0
3
Order By: Relevance
“…The prior case described a patient who experienced a near drowning and developed a fatal mycotic aneurysm with an associated brain abscess [20]. Near drowning appears to be the single most common risk factor in the reported cases of CNS infection from Scedosporium , occurring in approximately 20% of the cases [20, 21, 22, 23, 24, 25]. Our patient did not suffer a near drowning, but a history of fresh water exposure was not taken.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The prior case described a patient who experienced a near drowning and developed a fatal mycotic aneurysm with an associated brain abscess [20]. Near drowning appears to be the single most common risk factor in the reported cases of CNS infection from Scedosporium , occurring in approximately 20% of the cases [20, 21, 22, 23, 24, 25]. Our patient did not suffer a near drowning, but a history of fresh water exposure was not taken.…”
Section: Discussionmentioning
confidence: 97%
“…Intrathecal dosing is common in the treatment of fungal CNS infection, particularly for amphotericin B, as it limits systemic toxicity. Intrathecal amphotericin B was described in a case of S. apiospermum meningitis, but the patient died despite aggressive treatment [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Several authors, however, have suggested that the hypoxic state following submersion or the use of corticosteroids for treatment of aspiration pneumonia may compromise host immune responses, facilitating the penetration and spreading of the organism (108,109,283). The mode of fungal invasion in submersion victims is not always obvious.…”
Section: Epidemiology Of Human Infectionsmentioning
confidence: 99%
“…Infectious lesions in organs other than the CNS have been reported in 13 of the 21 cases, including in the lung (7 of 21, usually manifested as bronchopneumonia) (78,109,110,179,216,283,448), kidney (3 of 21) (108,110,283), eye (3 of 21, manifested as endophthalmitis or chorioretinitis) (110,283,473), musculoskeletal system (2 of 21, manifested as knee joint synovitis, femoral and tibial osteomyelitis, or spondylodiscitis) (110,144), heart (2 of 21) (108, 110), liver (283), skin (erythematous lesions with purplish-black necrotic centers in arms and abdomen) (110), and thyroid gland (110).…”
Section: Epidemiology Of Human Infectionsmentioning
confidence: 99%
See 1 more Smart Citation